2000
DOI: 10.1007/s002210000444
|View full text |Cite
|
Sign up to set email alerts
|

Vision of the hand and environmental context in human prehension

Abstract: Previous findings on the role of visual contact with the hand in the control of reaching and grasping have been contradictory. Some studies have shown that such contact is largely irrelevant, while more recent ones have emphasised its importance. In contrast, information arising from the surrounding environment has received relatively little attention in the study of prehensile actions. In order to identify the roles of both sources of information, we made kinematic comparisons between three conditions. In the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
46
3
2

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(62 citation statements)
references
References 24 publications
10
46
3
2
Order By: Relevance
“…Taken together, this would imply that contacting the object with the finger before the thumb represents a failure of collision avoidance, and our finding that finger-first contacts were generally 'hard' and imprecise is indicative of an error of this kind (see Melmoth et al, 2007). It would also explain a key finding in our glow-in-the-dark experiment; that subjects close both their digits more slowly (i.e., between peak grip and initial contact) when they cannot see their thumb -just as when visual feedback from the whole hand is unavailable (present results; Jakobson and Goodale 1991;Churchill et al 2000;Watt and Bradshaw 2000;Schettino et al 2003) -but make initial thumb contact with a wider grip aperture, because they are more cautiously closing just their finger when vision of this digit is selectively occluded.…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…Taken together, this would imply that contacting the object with the finger before the thumb represents a failure of collision avoidance, and our finding that finger-first contacts were generally 'hard' and imprecise is indicative of an error of this kind (see Melmoth et al, 2007). It would also explain a key finding in our glow-in-the-dark experiment; that subjects close both their digits more slowly (i.e., between peak grip and initial contact) when they cannot see their thumb -just as when visual feedback from the whole hand is unavailable (present results; Jakobson and Goodale 1991;Churchill et al 2000;Watt and Bradshaw 2000;Schettino et al 2003) -but make initial thumb contact with a wider grip aperture, because they are more cautiously closing just their finger when vision of this digit is selectively occluded.…”
Section: Discussionsupporting
confidence: 58%
“…The purpose of including the Full-light condition was to confirm that our subjects performed the task properly when allowed normal vision of their moving hand, the target and its immediate surroundings, and that removing this latter environmental information in the Whole Hand in-the-dark condition did not affect their performance in ways other than those expected from similar work (Churchill et al 2000). The mean kinematic data obtained (see Table 4) indicated that these expectations were met, as they replicated evidence that reducing the environment context in this latter condition resulted in slower movements (e.g., reduced peak reaching velocity; longer movement durations) and in larger grip sizes at peak and object contact, compared to normal performance in Full-light.…”
Section: Methodsmentioning
confidence: 87%
“…Possibly, seeing the entire hand within a full cue environment yields a more confident movement, which resulted in the adoption of a smaller margin of safety. In the same vein, movements performed with all cues available were much faster than those performed in the dark, indicating that participants achieved more confidence when able to see the object and the surrounding setting (Churchill et al 2000). In particular, by segmenting the movement in all its phases, we found that the effect of additional depth cues on the movement speed increased from the earlier to the later phases to be largest in the second part of the movement, during the deceleration phase.…”
Section: Discussionmentioning
confidence: 59%
“…Undoubtedly, the availability of different sources of feedback at the end of an action, like the vision of the hand and the physical presence of a target, plays a crucial role in guiding the limb to the appropriate contact position on the object (Jakobson and Goodale 1991;Gentilucci et al 1994;Connolly and Goodale 1999;Churchill et al 2000). As largely demonstrated, the absence of such feedback can induce atypical patterns of movements (Wing et al 1986;Gentilucci et al 1994;Churchill et al 2000;Bingham et al 2007;Hibbard and Bradshaw 2003;Bozzacchi et al 2014). These findings are in agreement with a theoretical framework postulating a nonmetric (i.e., non-Euclidean) representation of 3D properties.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation